2011
DOI: 10.1369/0022155411400874
|View full text |Cite
|
Sign up to set email alerts
|

Fluctuation of Aquaporin 1, 5, and 9 Expression in the Pig Oviduct during the Estrous Cycle and Early Pregnancy

Abstract: Thirteen mammalian aquaporin (AQPs) isoforms with a unique tissue-specific pattern of expression have been identified. To date, 11 isoforms of AQP have been reported to be expressed in female and male reproductive systems. The purpose of our study was to determine the localization and quantitative changes in the expression of AQP1, 5 and 9 within the pig oviduct during different stages of the estrous cycle and early pregnancy. The results demonstrated that AQP1, 5, and 9 were clearly detected in all studied st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 34 publications
(63 reference statements)
5
35
0
Order By: Relevance
“…Chen et al (2013) have demonstrated that E2 and P4 regulate different ultrastructural features of porcine oviduct epithelium cells, expression of selected genes, sperm-binding capacity and probably fluid movement patterns along the epithelium lining. Furthermore, aquaporins expression in oviduct (Skowronski et al, 2011) and spontaneous motility of organ (Rodriguez-Martinez et al, 1982) changes in the course of oestrous cycle in pigs, indicating regulation by steroid hormones. Hence, it can be suggested that, besides ovarian steroids, also locally produced oviductal steroids may be involved in the regulation of oviductal functions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Chen et al (2013) have demonstrated that E2 and P4 regulate different ultrastructural features of porcine oviduct epithelium cells, expression of selected genes, sperm-binding capacity and probably fluid movement patterns along the epithelium lining. Furthermore, aquaporins expression in oviduct (Skowronski et al, 2011) and spontaneous motility of organ (Rodriguez-Martinez et al, 1982) changes in the course of oestrous cycle in pigs, indicating regulation by steroid hormones. Hence, it can be suggested that, besides ovarian steroids, also locally produced oviductal steroids may be involved in the regulation of oviductal functions.…”
Section: Discussionmentioning
confidence: 98%
“…These steroids affect gene expression, cells ultrastructure and differentiation, motility of oviduct, as well as the composition and volume of oviductal fluid during the oestrous cycle (Rodriguez-Martinez et al, 1982;Buhi, 2002;Yaniz et al, 2006;Carrasco et al, 2008;Skowronski et al, 2011;Hunter, 2012). Thus, steroids regulate oviductal microenvironment and support maturation of gametes, fertilization and early embryonic development (Hunter et al, 1999;Wollenhaupt et al, 2001;Buhi, 2002;Georgiou et al, 2005;Brüssow et al, 2008;Chen et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Not all the oviductal NCs are secretory cells because some of them contain microvilli, which are covered with well-developed glycocalyx [11,60]. This suggests that NCs [61,62], which can be glycosylated [63][64][65]. AQPs take part not only in water transport but also in absorption or secretion of luminal fluid metabolites, thus maintaining a suitable environment for the reproductive functions.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that non-ciliated cells could be involved in absorptive phenomena which lead to the optimization of the luminal fluid for fertilization and embryonic development. As in other tissues, the absorptive activity of the intraluminal fluids occurring in the mammalian oviduct luminal surface is regulated by the aquaporins [67,68].…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, it is possible that altered resorptive phenomena may take place in the oviductal ampulla of superovulated ewes. It has been demonstrated that sex-steroid hormones regulate the expression of some aquaporins during the estrous cycle in rat [67] and pig [68] oviduct. The physical properties of the mucus within the oviduct change during the sexual cycle.…”
Section: A C C E P T E D Accepted Manuscriptmentioning
confidence: 99%